(untitled) (The Pakistan Development Review, 2010)
This paper examines the reasons for the early dominance of the bureaucratic élite in Pakistan and the downsizing that was brought about by the administrative reforms of 1973. The perceptions of bureaucrats and ministers indicate that loyalty to political establishment is now regarded a crucial requirement in a bureaucrat. This shift from the principle of political neutrality to the practice of political allegiance has affected both the development agenda as well as the institutions of the country.